Meningkatkan Kinerja Pemasaran Melalui Ekuitas Merek dan Penciptaan Nilai Bersama: Studi pada UMKM Kuliner Khas Lokal di Provinsi Banten - Riki Gana Suyatna (Jurnal Manajemen Riset Inovasi, 2024)
On a practical level, marketing performance is a key factor used to demonstrate the success of all areas of business. The Micro, Small and Medium Enterprises (MSMEs) sector is an industrial sector that can be relied on as an indicator of economic stability at both the local and national levels. The existence of the phenomenon of fluctuations in the growth and contribution of MSMEs certainly needs further investigation. This study aims to examine the effect of product innovation on marketing performance with brand equity and shared value creation as an intervening variable. The research sample was taken as many as 90 UMKM culinary typical of Banten local with non probability sampling technique, data analysis using SEM-PLS method. From the research results it is known that 1) product innovation has no impact on marketing performance; 2) product innovation has a positive and significant effect on shared value creation; 3) product innovation has a positive and significant effect on brand equity; 4) the creation of shared value has a positive but significant effect on marketing performance; 5) brand equity has a positive and significant effect on marketing performance. In addition, brand equity and shared value creation are able to mediate the relationship between product innovation and marketing performance